Daily life in the abyss - Tachjian, Vahé. (New York)
ix, 208, [2] sayfa
Keywords: “Historical research into the Armenian Genocide has grown tremendously in recent years, but much of it has focused on large-scale questions related to Ottoman policy or the scope of the killing. Consequently, surprisingly little is known about the actual experiences of the genocide’s victims. Daily Life in the Abyss illuminates this aspect through the intertwined stories of two Armenian families who endured forced relocation and deprivation in and around modern-day Syria. Through analysis of diaries and other source material, it reconstructs the rhythms of daily life within an often bleak and hostile environment, in the face of a gradually disintegrating social fabric“ --